2018
DOI: 10.1111/tmi.13084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SD bioline cholera rapid diagnostic test during the 2016 cholera outbreak in Lusaka, Zambia

Abstract: The observed sensitivity and specificity were within recommendations set by the Global Task Force for Cholera Control on the use of cholera RDT (sensitivity = 90%; specificity = 85%). Although the sample size was small, our findings suggest that the SD Bioline RDT could be used in the field to rapidly alert public health officials to the likely presence of cholera cases when an outbreak is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Previous qualitative studies showed that economic burden due to MDR-TB treatment was a reason for low enrollment26,27 and treatment interruption 6. Another study found that financial support motivated patients to improve adherence28 and had a positive effect on successful treatment 5. Therefore, revising the national essential drug list and preparing a special budget to universally cover all drugs in the list, including injection fees, may be beneficial to optimize treatment regimens and improve adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous qualitative studies showed that economic burden due to MDR-TB treatment was a reason for low enrollment26,27 and treatment interruption 6. Another study found that financial support motivated patients to improve adherence28 and had a positive effect on successful treatment 5. Therefore, revising the national essential drug list and preparing a special budget to universally cover all drugs in the list, including injection fees, may be beneficial to optimize treatment regimens and improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only four studies have reported data on treatment interruption among patients with MDR-TB 36. Treatment interruption was defined as an interruption of any anti-TB drug for at least one day at any time during the treatment course while a serious treatment interruption lasting for more than two consecutive weeks but less than two consecutive months 3,5,6. The incidence of treatment interruption ranged from 68% to 93% and the incidence of serious interruption was 17%6 and 27%.5 Serious treatment interruption was demonstrated to be associated with unsuccessful treatment outcome 3,4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholera has been present and recurring in Zambia since 1977 [ 1 ]. In Zambia and in most sub-Saharan countries, cholera is diagnosed using stool culture, serology and rapid diagnostic tests (RDTs) [ 2 ]. However, culture and RDTs do not provide the genetic relatedness or diversity information that is critical to having insight into whether the outbreaks are seeded from existing local isolates or if the outbreaks represent separate transmission events, hence, the need to have genetic data in addition to culture and RDT data.…”
Section: Introductionmentioning
confidence: 99%
“…The O139 line on this test has been reported to give false positives [ 3 , 12 , 13 ] and given that O139 rarely circulates, its inclusion in the test may be more of a nuisance than an asset. The SD Bioline O1 test has demonstrated field sensitivity of 81.1%–90.9% and specificity of 92.8%–95.2% when performed directly, with increases in both after enrichment [ 14 , 15 ]. Both the Crystal VC and SD Bioline tests detect the lipopolysaccharides (LPS) antigens of V. cholerae using the precoated monoclonal antibodies specific to V. cholerae O1 and/or O139.…”
mentioning
confidence: 99%